Harga, Promosi, Ulasan dan Foto Produk terhadap Keputusan Pembelian E-Commerce - Ang Reny; Dwisason Tandiono; Calvin Calvin; Winda Sri Astuti (IPM2KPE, 2023)
The purpose of this study was to test and analyze the effect of price, promotion, product reviews and photos on E-Commerce purchases at Shopee. This research method is quantitative using survey research on case studies at PT Shopee International Indonesia. Data analysis used simple linear regression analysis. The results showed, a) a significant value for testing the effect of price on purchasing decisions obtained a sig value of 0.365 <0.05 with a Î² value of 0.131; b) a significant value for testing the effect of promotion on purchasing decisions obtained a sig value of 0.000 <0.05 with a Î² value of 0.614; c) a significant value for testing the effect of reviews on purchasing decisions obtained a sig value of 0.694 > 0.05 with a Î² value of 0.044; d) a significant value for testing the effect of product photos on purchasing decisions obtained a sig value of 0.494 <0.05 with a Î² value of 0.071. Conclusion, a) there is a positive effect of price on purchasing decisions; b) there is a positive effect of promotion on purchasing decisions; b) there is a positive influence of product reviews and photos on purchasing decisions; c) there is a positive influence of price, promotions, reviews and product photos on purchasing decisions. Keywords: Price, Purchase Decision, Promotion, Reviews and Product Photos